Loss of RAP2A Aggravates Cartilage Degradation in TMJOA via YAP Signaling. (March 2023) - Qi, H.; Zhang, Y.; Xu, L.; Zheng, X.; Li, Y.; Wei, Q.; Li, Y.; Zhao, Z.; Fang, J.
Abnormal stress loading has been considered a major contributor to the initiation of temporomandibular joint osteoarthritis (TMJOA), but studies to date have not identified a functional molecule that transforms physical stress into biological or biochemical signaling in chondrocytes in response to excessive mechanical stress. Ras-related protein Rap-2a (RAP2A) is reportedly a molecular switch that relays extracellular matrix rigidity signals via the Hippo/Yes-associated protein (YAP) pathway. In the present study, RAP2A diminished with cartilage degradation in unilateral anterior crossbite-induced TMJOA mice, as well as severe cartilage matrix degeneration and TMJOA formation in Cre-loxP–mediated conditional RAP2A knockout mice. RAP2A in chondrocytes regulated the Hippo/YAP pathway directly in response to matrix stiffness, and RAP2A/Hippo/YAP was critical for a chondrocyte phenotype switch and matrix synthesis function. Loss of RAP2A impaired cartilage homeostasis and altered chondrocyte phenotype via Hippo/YAP/SRY-box transcription factor 9 signaling. It may be possible to generate therapeutic strategies using RAP2A or YAP to attenuate the TMJOA pathological process at an early stage. This is the first study to reveal the molecular function of RAP2A in TMJOA progression as a mechanotransduction molecule in condylar chondrocytes.